The Breakup of the Bell System and its Impact on US Innovation - Martin Watzinger; Monika Schnitzer (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
We analyze the effects of the 1984 breakup of the Bell System on the rate, diversity, and direction of US innovation. In the antitrust case leading to the breakup, AT&T, the holding company of the Bell System, was accused of using exclusionary practices against competitors. The breakup was intended to end these practices. After the breakup, the scale and diversity of telecommunications innovation increased. Total patenting by US inventors related to telecommunications increased by 19%, driven by companies unrelated to the Bell System. Patenting by Bell's successor companies decreased, but not the number of top inventions.
Keywords: O30; K21; L40; 330; antitrust; innovation; diversity; exclusionary practices